Implicit Causality and Pronoun Resolution in Intersubjective Discourse Relations - Lyu, Siqi; Wang, Luming (Frontiers in Psychology, 2022)
Interpersonal verbs like disappoint and praise in Lucy disappointed/praised Mary because she… bias the potential cause of the event to one of the antecedent NPs (e.g., Lucy for disappoint whereas Mary for praise). Using Chinese as its materials, this study investigates how verb-based implicit causality affects online pronoun resolution in backward concession (e.g., Lucy disappointed/praised Mary although she…), an intersubjective discourse relation where the subordinate although-clause forms an indirect relationship with the preceding main clause. Experiment 1 was a baseline experiment with the typical structure where implicit causality is found to be effective, i.e., backward causality. Results showed a clear modulation effect of implicit causality on pronoun resolution such that as verb bias strength decreases, participants were faster in processing sentences that disambiguate the pronoun to the verb-inconsistent NP. This modulation effect, however, was not observed in Experiment 2 where we used the same verbs but replaced because with although. There was no preference for the pronoun to be disambiguated towards the verb-consistent NP or the verb-inconsistent NP in backward concession. The results of Experiments 1 and 2 were replicated in Experiment 3 where we directly compared causal and concessive relations. We attribute the absent effect of verb-based implicit causality in backward concession to the intersubjective nature of the concessive relation. Discourse devices such as although indicate speakers’ subjective perspective and comprehenders are able to quickly accommodate the speaker’s point of view during online discourse processing.